THE INTENTION TO SWITCH CONVENTIONAL BANK CUSTOMERS TO DIGITAL BANKS DEVELOPMENT IS SUCCESS MODEL - Habsy Qorisu Nurhafidz; Ignatius Hari Santoso; Bambang Sutedjo (Jurnal Ekonomi, 2023)
This study aims to determine the effect of system quality, information quality, service quality, and gender on the intention to switch BCA customers. The population used is BCA customers in 2023. The samples taken in this study were 100 consumers. Sampling using purposive sampling. Data analysis using multiple regression analysis. The results showed that system quality, information quality and service quality had a positive and significant effect on switching intentions. And gender has no effect and is not significant on switching intentions.